Analysis of patent records related to the prevention and signaling of falls in Brazil - Alves, Renata Camargo [UNESP]; Colichi, Rosana Maria Barreto [UNESP]; Lima, Silvana Andrea Molina [UNESP] (My University, 2023)
Objective: To analyze patent records aimed at preventing and signaling falls in a Brazilian database. Method: Electronic documentary research carried out in the database of the Instituto Nacional da Propriedade Industrial using the word “fall” in the search resource. Patent records related to the prevention and signaling of falls at home and in care environment applied from 2000 to 2021 were included. Tabulated data were evaluated using absolute/relative frequencies. Results: From the 45 patents, 91% were published starting from 2011, with an average of 1214 days between application and publication, 11% of applicants were from public universities and 9% of the inventors were nurses, physician or physical therapists. Conclusion: There was a delay in the publication of the patents and small participation of researchers linked to the academic area and health professionals, revealing the need to equip universities and health services in order to guarantee the development of innovations.
Análisis de registros de patentes relacionados con la prevención y señalización de caídas en Brasil
Análise dos registros de patentes relacionadas à prevenção e sinalização de quedas no Brasil
Keywords: Accidental falls; Patent; Patient safety; Science, technology and innovation indicators